2021
DOI: 10.3390/children8010025
|View full text |Cite
|
Sign up to set email alerts
|

Play in Children with Neurodevelopmental Disorders: Psychometric Properties of a Parent Report Measure ‘My Child’s Play’

Abstract: Play is essential in childhood, allowing for a positive trend in development and learning. Health professionals need useful tools to assess it, especially in the case of children with neurodevelopmental disorders. The aim of this study was to validate and cross-culturally adapt the My Child’s Play questionnaire and to find out if this instrument allows us to differentiate the play of children with neurodevelopmental disorders from the play of children with neurotypical development. A total of 594 parents compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Parental play supportiveness was assessed by items extracted from the My Child's Play questionnaire (Schneider & Rosenblum, 2014). This measure has been employed in both international (e.g., Romero‐Ayuso et al., 2021) and local (e.g., W. K. Fung & Chung, 2021) research with kindergarten children. Six items from the play choices and preferences subscale tapping parents’ beliefs in and day‐to‐day practices of play (e.g., “I consider my child's play preferences,” “Daily routine includes time for playing with child”) were employed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Parental play supportiveness was assessed by items extracted from the My Child's Play questionnaire (Schneider & Rosenblum, 2014). This measure has been employed in both international (e.g., Romero‐Ayuso et al., 2021) and local (e.g., W. K. Fung & Chung, 2021) research with kindergarten children. Six items from the play choices and preferences subscale tapping parents’ beliefs in and day‐to‐day practices of play (e.g., “I consider my child's play preferences,” “Daily routine includes time for playing with child”) were employed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Sport activities are crucial for children's development and for learning good behavior [11][12][13][14][15]. During childhood, sports may prevent future pathologies, and these activities are essential for the social inclusion and psychological well-being of the child [16][17][18]. Moreover, it has been shown that young sport practitioners have improved quality of life [11], brain cortical excitability [12], long-term neural adaptation mechanisms, and visuo-spatial capacities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Each item is rated on a 5-point Likert scale, where higher scores reflect better play performance. In addition, a cut-off score of <142 on the MCP scale was indicative of atypical play associated with the presence of neurodevelopmental disorders (NDD-play) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MCP has acceptable internal consistency, construct validity and discriminant validity for Spanish children with and without neurodevelopmental conditions (internal consistency: Cronbach’s alpha = 0.695; construct validity: root mean square error of approximation = 0.023 (95% CI = 0.010–0.050), comparative fit index = 0.991, non-normed fit index = 0.990, root mean square of residuals = 0.048; discriminant validity: area under the curve = 0.876 (95% CI = 0.840–0.912)) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%